Revitalizing Strategic Agility in a Turbulent Environment: A Conceptual Discourse - Godwin , Poi; Sorbarikor , Lebura (International Journal of Scientific Research and Management (IJSRM), 2022)
This paper conceptually examined revitalizing strategic agility in a turbulent environment. In the current turbulent and highly competitive environment of today, agility, that is the ability of organizations to quickly sense and respond to environmental changes, is an important determinant of organizational success. With the advancement of information technologies, company strategy focuses nowadays on sustainable competitive advantage, and gives importance to short-term advantages of flexibility and fast response. In the unpredictable and competitive world of today, organizations must have different competitive features to compete; otherwise, they will move towards annihilation. One of the capabilities that organizations need in the turbulent environments of today is agility. Strategic agility is the ability to continuously and adequately adjust and adapt in appropriate time the strategic direction in core business in relation to changing circumstances. Agility provides the organization with the possibility of quick response and compatibility with environment and allows the organization to improve its efficiency.  The paper is largely conceptual in nature and adopts a desk research methodology in reviewing extant literature. This study concludes that firms operating in dynamic environments must realize the need for change and adaptation and thereby stimulate their in developing agility that can better respond to a dynamic environment.